2013
DOI: 10.1098/rstb.2012.0481
|View full text |Cite
|
Sign up to set email alerts
|

Phenological response of tundra plants to background climate variation tested using the International Tundra Experiment

Abstract: The rapidly warming temperatures in high-latitude and alpine regions have the potential to alter the phenology of Arctic and alpine plants, affecting processes ranging from food webs to ecosystem trace gas fluxes. The International Tundra Experiment (ITEX) was initiated in 1990 to evaluate the effects of expected rapid changes in temperature on tundra plant phenology, growth and community changes using experimental warming. Here, we used the ITEX control data to test the phenological responses to background te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
179
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(194 citation statements)
references
References 43 publications
(74 reference statements)
13
179
1
1
Order By: Relevance
“…There is still uncertainty surrounding the relative response of different PFTs to future climate change (Elmendorf, Henry, Hollister, Bjork, Bjorkman, et al., 2012), especially that of phenology (Oberbauer et al., 2013); however, evidence thus far would imply that deciduous shrubs that are already present in the tundra represent the most negative future competitive interaction to E. vaginatum . Common tundra shrubs such as Betula nana have been shown to exhibit developmental plasticity (e.g., increased branching, canopy density) in response to release from abiotic stress (Bret‐Harte et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still uncertainty surrounding the relative response of different PFTs to future climate change (Elmendorf, Henry, Hollister, Bjork, Bjorkman, et al., 2012), especially that of phenology (Oberbauer et al., 2013); however, evidence thus far would imply that deciduous shrubs that are already present in the tundra represent the most negative future competitive interaction to E. vaginatum . Common tundra shrubs such as Betula nana have been shown to exhibit developmental plasticity (e.g., increased branching, canopy density) in response to release from abiotic stress (Bret‐Harte et al., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While there were differences in the timing of senescence between ecotypes, there was no significant effect of warming on timing of senescence, a finding that concurs with other warming studies (Bjorkman, Vellend, Frei, & Henry, 2017; Rosa et al., 2015) as well as long‐term datasets which show that phenology of arctic plants is relatively unresponsive to recent climate change (Oberbauer et al., 2013). A long‐term warming experiment also found that phenology of high arctic plants was not responsive to warming, but year‐to‐year variation in phenology could be explained by snowmelt date (Bjorkman, Elmendorf, Beamish, Vellend, & Henry, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Air temperature changes have been documented to alter the annual phenological progression of Arctic plant habitats, with warming being a primary driver of growth period extension [4,5,31]. Graminoid-and shrub-dominated habitats have a larger response to variations of the daily average temperatures in June and August compared to other habitat types.…”
Section: Interannual Variations In Daily Average Temperaturesmentioning
confidence: 99%
“…Arctic plant habitats are characterized by high spatial heterogeneity, often at relatively small scales (submeter), in response to moisture gradients, limiting the ability to predict phenological changes detected by remote sensing at the landscape scales [25][26][27]. Although the vegetation in some regions of the Arctic is well studied, with many studies documenting shifts in habitat type, NDVI, productivity, and phenology in recent decades [17,21,23,[28][29][30][31], most of these data were collected once, twice, or very rarely three times per week. As a result, few studies to date have investigated the role of daily air temperatures on the short-term progression of greening and senescence in tundra habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Passive warming [1][2][3][4][5][6][7]. Previous warming studies using OTCs have been directed toward analyzing specific species responses [8], radiation dynamics [9], plant phenology [10], snow regime shifts [11], and trace gas exchange [12,13] to name a few.…”
Section: Introductionmentioning
confidence: 99%